Pembelajaran Bagi Siswa Berkebutuhan Khusus Tunarungu di SLB Negeri Keleyan - Aini Zahrok; Nova Estu Harsiwi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to get an idea of ​​how learning is carried out for deaf students at the Keleyan State Special School. This research was conducted using a descriptive qualitative method. In collecting data, researchers used data collection techniques in the form of interviews, observation and documentation. The research results show that the learning process for deaf students has been well designed by the teacher starting from the planning, implementation and assessment stages. The implementation of learning for deaf students is adaptive, meaning that learning is adjusted to the students' conditions and needs. So the implementation of learning for deaf students can be said to be quite ideal.